DIGITAL TOOLS FOR MANAGING ACADEMIC TASKS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article looks at how students can manage their academic work more effectively with the help of contemporary digital tools including task-management software, AI writing assistants, and learning analytics systems. The study, which is based on recent research (2022–2025), emphasizes how digital learning platforms and productivity tools have improved academic results, motivation, and organization.